Management of Stress Urinary Incontinence - Cornella, Jeffrey L (MedReviews, LLC, 2004)
Although there is renewed interest in conservative therapies for stress urinary incontinence, such as pelvic floor exercises, electrical stimulation, and duloxetine therapy, surgery remains the primary choice in managing this condition. Surgical options include paravaginal defect repair, the Marshall-Marchetti-Krantz procedure, open and laparoscopic Burch urethropexy, and pubovaginal sling procedures. There is a growing trend in the United States toward use of the pubovaginal sling procedure as the primary operation for urinary incontinence due to less invasive techniques. Studies comparing the pubovaginal sling with open urethropexy have shown similar short-term cure rates. More large prospective, randomized studies are needed to assess long-term rates.